The Learning Environment and Students’ Learning Interest in Online Learning - Dahniar Ramadani; Siti Suharni Simamora (Scientiae Educatia: Jurnal Pendidikan Sains, 2022)
This study aims to investigate the relationship between the learning environment and students' interest in online classes in State Senior High School 1 of Sei Kanan in Class X-Science. This correlational study employs a qualitative descriptive approach. This study's population consisted of all 72 students, with 36 students from Class X-Science 1 and 36 students from Class X-Science 2 serving as samples. Techniques and data collecting techniques employed were questionnaires. The results obtained from the learning environment and student interest in learning were quite good, with a good learning environment that was very conducive to the success of students in learning and a clean, comfortable, fresh, and bright learning atmosphere that was sufficient to create a pleasant learning atmosphere, in addition to a high level of student interest in learning. In this instance, a good learning environment would undoubtedly facilitate the easy implementation of learning with a comfortable learning environment that will interest and engage students in learning.